Predictors of Zero X-Ray Ablation for Supraventricular Tachycardias in a Nationwide Multicenter Experience. (March 2018) - Pani, Antonio; Giuseppina, Belotti; Bonanno, Carlo; Grazia Bongiorni, Maria; Bottoni, Nicola; Brambilla, Roberta; Ceglia, Sergio de; Della Bella, Paolo; Vito, Giovanni de; Malaspina, Daniele; Menardi, Endrj; Napoli, Velia; et al.
Abstract : Background: This multicenter, prospective study evaluated the determinants of zero-fluoroscopy (ZFL) ablation of supraventricular tachycardias. Methods and Results: Four hundred thirty patients (215 male, 55.4±22.1 years) with indication to electrophysiological study or ablation of supraventricular tachycardias were enrolled. All participating physicians agreed to follow the as low as reasonably achievable policy. A procedure was defined as ZFL when no fluoroscopy was used. The total fluoroscopy time inversely correlated to the number of procedures previously performed by each operator since study start ( r =−0.112; P =0.02). Two hundred eighty-nine procedures (67.2%) were ZFL; multivariable analysis identified as predictors of ZFL: procedure after the 30th for each operator, compared with procedures up to the ninth ( P =0.011; hazard ratio, 3.49; 95% confidence interval [CI], 1.79–6.80); the type of arrhythmia ( P =0.031; electrophysiological study and atrioventricular nodal reentry tachycardia ablation having the highest probability of ZFL; hazard ratio, 6.87; 95% CI, 2.08–22.7 and hazard ratio, 2.02; 95% CI, 1.04–3.91, respectively); the operator's ( P =0.002) and patient's age ( P =0.009). Among operators, achievement of ZFL varied from 0% to 100%; 8 (22.8%) operators achieved ZFL in <25% of their procedures; 17 (48.6%) operators achieved ZFL in >75% of their procedures. The probability of ZFL increased by 2.8% (hazard ratio, 0.98; 95% CI, 0.97–0.99) as patient's age decreased by 1 year. Acute procedural success was obtained in all cases. Conclusions: The use of 3-dimensional mapping system completely avoided the use of fluoroscopy in most cases, with very low fluoroscopy time in the remaining and high safety and effectiveness profiles. Achievement of ZFL was predicted by the type of arrhythmia, operator's experience, and patient's age.